Energy center selection in G7 industry with fuzzy MOORA - Yüksel, Serhat; Mikhaylov, Alexey; Khomyakova, Lyubov (IGI Global, 2021)
In this study, energy center selection of G7 countries is examined. In this context, firstly, the studies in the literature have been evaluated in detail, and seven different criteria have been determined which may affect this selection. Taking these seven different criteria into consideration, G7 countries are ranked by fuzzy MOORA method according to energy center selection performance. According to the results, Japan and Germany are the most successful countries. On the other hand, it was concluded that France and Italy ranked last in terms of energy center selection performance. Hence, especially the countries in the last rankings should be more careful in selecting energy center. In this framework, the customer potential, the training profiles of the customers, the potential of the company with investment demand, the previous payment performance of these companies, and the market risks should be considered by the energy companies while opening new branches.
Keywords: MOORA; Fuzzy MOORA; G7 Industry